PROFESSIONAL STATUS AND THE PERSONNEL FUNCTIONARY IN THE SADF - Eberlein, R. (Scientia Militaria - South African Journal of Military Studies, 2012)
Introduction During the last year or so there has developed an increasing awareness among personnel functionaries in the SA Defence Force of a movement aimed at obtaining recognition of the professional status of the personnel function. Several members of the SADF have already applied for and been granted such recognition by the SA Board for Personnel Practice, a non-statutory body for the voluntary registration of personnel people who meet certain professional standards. Why have these people voluntarily subjected themselves to an assessment of their professional worth and what do they hope to gain from registration, from professional recognition? This paper attempts to answer those and certain other pertinent questions.